Strengthening Tourism Destination Resilience Through Health, Safety, and Security: A Case Study of Batu Karas Beach, Pangandaran - Dhahiyat, Ahmad Prawira; Mulyana, Hadi; Hehanussa, Akib; Lazuardina,, Annisa; Gusdi, Taqiy (PT. Hafasy Dwi Nawasena, 2026)
Batu Karas Beach is a prominent marine tourism destination in Pangandaran, Indonesia, renowned for its surf-grade wave characteristics. However, these physical attributes harbor significant environmental risks, necessitating a robust safety management framework. This study employs a descriptive qualitative approach to evaluate the implementation of Occupational Safety, Health, and Security as a fundamental instrument of destination resilience. The conceptual framework integrates spatial-temporal visitor dynamics with hazard identification, specifically targeting dominant risk factors such as rip currents and breaking waves. The research further assesses the functional effectiveness of the Life Guard (Balawista) in incident mitigation and emergency response. Analysis reveals a critical discrepancy between field officer ratios and visitor fluctuations during peak seasons. While a supervisory structure exists, this operational imbalance increases maritime vulnerability and potential accident rates. The current safety infrastructure remains largely traditional, lacking integration with modern preventive systems. Research findings recommend integrating digital technologies such as QR-Code-based information systems and modernizing safety equipment to strengthen Health Safety and Security standards. Enhancing personnel capacity through international certification and preventive education for tourists are crucial prerequisites for establishing Batu Karas Beach as a safe, globally competitive, and sustainable destination.